(untitled) (Gestión y Gerencia, 2024)
The purpose of this article was to diagnose the capabilities profile of companies in the road construction subsector of Barquisimeto, Lara state, based on the steps of the tools Profile of Opportunities and Threats in the Environment (POAM) and Profile of Internal Capabilities (PCI) developed by Serna (2016), to face the scenario characterized by the Covid-19 Pandemic in 2020, where environmental factors exponentially impacted the performance of these organizations due to the great human losses and the partial paralysis of the economy, causing delays in the contracting and execution of works; a situation that demands management to implement new strategies to achieve its objectives. The study is based on quantitative, descriptive field research, considering as a unit of analysis four companies registered in the National Registry of Contractors and that at that time had contracts with public agencies, to which a questionnaire was applied for this purpose. It is concluded that the COVID-19 pandemic situation was marked by a high level of uncertainty, subject to the national emergency decree, while, from an internal point of view, there was a low level of management autonomy, honor in compliance with decrees and regulations in contractual compliance for each of the works.